2017
DOI: 10.1007/s12088-017-0670-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Antimicrobial Properties of Chitosan–Silver Nanocomposites Films Against Fish Pathogenic Bacteria and Fungi

Abstract: Development of nanostructured films using natural polymers and metals has become a considerable interest in various biomedical applications. Objective of the present study was to develop silver nano particles (AgNPs) embedded chitosan films with antimicrobial properties. Based on the Ag content, two types of chitosan silver nano films, named as CAgNfs-12 (12 mM) and CAgNfs-52 (52 mM) were prepared and characterized. Field emission scanning electron microscope (FE-SEM) images of two CAgNfs showed the circular A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For example, Liu, et al [65] reported that surface grafting of gentamicin molecules improved antibacterial chitosan properties [65]. In another study, chitosan films incorporated with Ag nanoparticles exhibited enhanced antimicrobial properties (Figure 6) [66]. Chitosan's wound-healing properties are enhanced in Ag-chitosan.…”
Section: Chemical Modifications On Chitin and Chitosan Surfaces: Deve...mentioning
confidence: 97%
“…For example, Liu, et al [65] reported that surface grafting of gentamicin molecules improved antibacterial chitosan properties [65]. In another study, chitosan films incorporated with Ag nanoparticles exhibited enhanced antimicrobial properties (Figure 6) [66]. Chitosan's wound-healing properties are enhanced in Ag-chitosan.…”
Section: Chemical Modifications On Chitin and Chitosan Surfaces: Deve...mentioning
confidence: 97%
“…Antibacterial activity: The agar disc diffusion method was employed for the determination of the antibacterial activity of the Ag-CS-AA NC 28 . Agar medium (Mueller-Hinton) was prepared by adding beef infusion solids (0.2 g), starch (15 g), casein hydrolysate (1.75 g) and agar (1.7 g) in 100 mL distilled water.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…For example, Liu et al postulated that the surface grafting of gentamicin molecules improved the antibacterial properties of CS [59]. Dananjaya et al developed AgNP-(Ag nanoparticle-) embedded chitosan films with more optimal antimicrobial properties [60].…”
Section: Antibacterial Performancementioning
confidence: 99%